Effects of population density on adult morphology and life-history traits of female Mediterranean flour moth, Ephestia kuehniella (Lepidoptera: Pyralidae) - Bhavanam S; Trewick SA (Institute of Entomology, Biology Centre, Czech Academy of Science, České Budějovice, 2022)
Intraspecific competition and food shortage due to high population density during early life can have a profound effect on adult fitness.Organisms often mitigate negative effects of high population density by adjusting resource allocation to adult morphological and life-history traits. In Lepidoptera with short-lived adults that do not feed, it is predicted that females developed from dense larval aggregations invest more in reproduction and traits linked to offspring survival. Here, we investigated the effects of larval population density on adult morphology and life-history traits in the female Mediterranean flour moth, Ephestia kuehniella by raising larvae at a range of population densities. Adults from high population density (16 larvae per g of food) had smaller head, thorax, and forewing compared to other densities. The allometric slope of forewing length with body mass did not differ among population densities, indicating no changes in adult wing morphology at high population density. However, we found that females emerged from larvae at high population density had bigger abdomens relative to body mass, indicating resource investment in reproduction, probably to mitigate the negative effects of crowding on egg production. Ovipositor length did not differ among population densities, indicating conservation of resources to structures with egg-laying function that affect offspring survival. Taken together, these results suggest that female E. kuehniella responding to high larval population density invest relatively more in reproduction, a life-history strategy that could alleviate negative effects of population density on fitness. This study also highlights the importance of a species’ reproductive strategy in its adaptive response to environmental conditions, which is relevant to many capital breeders dependent on larval resources for reproduction.
Keywords: Reproduction; allometry; trade-off; nutrition